1996
DOI: 10.1111/j.1600-0773.1996.tb01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Changes in Glutathione Metabolism and Lipid Peroxidation Induced by Swimming are Partially Prevented by Melatonin

Abstract: The present study used male Sprague-Dawley rats to investigate changes in glutathione [reduced (GSH) and oxidized GSH (GSSG)]. lipid peroxidation (as indicated by tissue levels of malonaldehyde and 4-hydroxyalkenals), and the activity of the antioxidant enzyme glutathione peroxidase after a bout of swimming (30 min.) with or without melatonin (N-acetyl-5-methoxytryptamine) treatment. In muscle, the concentration of GSH and the GSH/GSSG ratio were decreased following 30 min. of swimming: these changes are indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 31 publications
1
33
0
1
Order By: Relevance
“…This result indicates that melatonin administration signifi cantly increased GSH levels in an acute swimming exercise. The fact that melatonin administration to rats subjected to a half-hour acute swimming exercise was shown to increase levels of GSH in various tissues, in comparison to the exercise group, which was not administered melatonin (27), is consistent with high GSH levels we found in our study.…”
Section: Discussionsupporting
confidence: 91%
“…This result indicates that melatonin administration signifi cantly increased GSH levels in an acute swimming exercise. The fact that melatonin administration to rats subjected to a half-hour acute swimming exercise was shown to increase levels of GSH in various tissues, in comparison to the exercise group, which was not administered melatonin (27), is consistent with high GSH levels we found in our study.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that senescence entails a decrease in the antioxidant defence system [43]. Hara et al [44] found an elevation of GPx activity in liver and muscle after a swimming test.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue samples were centrifuged with Yellow Line DI 18 basic. The homogenates were centrifuged at 15,000 rpm for 15 min at +4 • C. Supernatants were collected and frozen at −80 • C until time of assay (Hara et al, 1996).…”
Section: Biochemical Examinationmentioning
confidence: 99%